High oxygen and SNG injection in blast furnace ironmaking with Power to Gas integration and CO2 recycling. (15th June 2023) - Perpiñán, Jorge; Bailera, Manuel; Peña, Begona; Romeo, Luis M.; Eveloy, Valerie
Abstract: In the last years, reduction of CO2 emissions from the steel industry has been of great importance. Carbon capture, oxygen blast furnaces and top gas recycling technologies, among others, have been deeply studied as low carbon solutions. In this paper, a novel integration of carbon capture and power to gas technologies in the steelmaking industry is presented. Green hydrogen via proton exchange membrane (PEM) electrolysis and CO2 via methyldiethanolamine (MDEA) scrubbing from the blast furnace gas (BFG) are used to produce synthetic natural gas in an isothermal fixed bed methanation plant. The latter gas is injected into the blast furnace, closing a carbon loop and reducing coal consumption. The oxygen by-produced in the electrolyser covers the entire oxygen demand of the steelmaking plant and avoids the need for an air separation unit (ASU). The novelty of this work relies on the variation of the oxygen enrichment and its temperature in the hot blast, and how it influences the power to gas integration concept. This power to gas integration is compared with a conventional BF-BOF plant from a technical, economic, energy and environmental point of view. Both plant process configurations were implemented in Aspen Plus simulations, assessing the fossil fuel demand, energy penalty, cost and CO2 emissions. Emission reduction up to 34% can be achieved with power to gas integration, with an energy penalty of 17 MJ/tHM and a cost of 352 €/tCO2 . Highlights: Novel concept of power to gas integration in the steel industry. Indirect electrification of the steel industry. CO2 and coal use reductions up to 34 and 33%, respectively. Improved fulfilment of downstream energy requirement needs. CO2 abatement cost of 52 and 233 € per ton of hot rolled coil.